The third way: the contribution of academic quality assurance third spacers to ‘pedagogical partnership’ - Katie Akerman; Ceri Hunter (Journal of Learning Development in Higher Education)
This case study uses a ‘lived experience’ account of a pivot from a conventional academic quality and standards approach to a progressive pedagogic partnership in a small Cathedrals Group university. We first contextualise our pivot within the recent history of academic quality assurance in the sector. We consider the evolution of ourselves as third spacers in informing and shaping the practice of academic colleagues through our third-space knowledge and experience (Whitchurch, 2012) in conjunction with the introduction of V5, ‘collaborate with others to enhance practice’, in the UK Professional Standards Framework 2023 (AdvanceHE, 2023). We explore how quality is used to leverage the advancement of positive student experiences and outcomes from a new perspective, and how we are seeking to resolve tensions between the characteristics of convention and progression (and positive disruption) to develop learning points for success.